THE DEVELOPMENT OF COMMUNICATIVE LANGUAGE TEACHING IN MEDICAL ENGLISH CLASSE (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
The present article studies the implementation ways of CLT activities into the classroom. The actuality of this paper is the investigation of some typical CLT activities in the way of development of the speaking skills to provide communication in learning a foreign language in the field of medicine and making EFL classroom more effective teaching environment as facilitator.